COMBINATION DESIGN OF KNOWLEDGE DIMENSIONS AND THINKING PROCESS LEVELS ON PARABOLIC MOTION LEARNING DEVICES FOR PHYSICS LEARNING IN PEKANBARU CITY HIGH SCHOOL - Jeremia Vincensius; Amali Putra; - Murtiani; - Hidayati (PILLAR OF PHYSICS EDUCATION, 2022)
The 2013 curriculum for high school physics lessons mandates teachers to change learning patterns that are "tell" to "find out" through a combination of various dimensions of knowledge and levels of thinking processes that students must master. It’s hoped that through learning, there will be an increase in students' knowledge competence and thinking process abilities. The initial study results indicate the need for a design of a combination of knowledge dimensions and levels of thinking processes in the form of learning devices. This study aims to develop a learning device design oriented to the combination of the dimensions of knowledge and the level of the thought process of parabolic motion material for physics learning at SMAN in Pekanbaru City. The type of research is Research and Development (R&D), with the ADDIE development model reduced to the development stage. This study involved three physics lecturers, FMIPA UNP, as expert judgment and learning practitioners, namely three physics teachers at SMAN 2, 7, and 12 Pekanbaru. The research object is lesson plans, teaching materials, and evaluation instruments. The results showed that the theoretical validity of learning devices consisting of lesson plans, teaching materials, and evaluation instruments according to the expert team was 0.74 and was in the medium category or with valid interpretations. According to the practitioner team, the theoretical practicality of learning devices was 0.96 and is in the high category or very practical. Thus, the learning device can be continued with field trials to learn physics at SMAN in Pekanbaru City.